Benchmarking Nutraceutical Soybean Composition Relative to Protein and Oil - Carrera, Constanza S.; Salvagiotti, Fernando; Ciampitti, Ignacio A. (Frontiers in Nutrition, 2021)
The aim of this study was to explore relationships between protein, oil, and seed weight with seed nutraceutical composition, focused on total isoflavone (TI) and total tocopherol (TT) contents across genotypic and environmental combinations in soybean. We conducted a synthesis-analysis of peer-reviewed published field studies reporting TI, TT, protein, oil, and seed weight (n=1908). The main outcomes from this synthesis-analysis were: i) relationship of TI-to-protein concentration was positive, though for the upper boundary, TI decreases with increases in protein; ii) relationship of TT-to-oil concentration was positive, but inconsistent when oil was expressed in mg per seed; and iii) as seed weight increased, TI accumulation was less than proportional relative to protein concentration and TT decreased more proportional relative to oil concentration. Association between nutraceuticals and protein, oil, and seed weight for soybean reported in the present study can be used as a foundational knowledge for soybean breeding programs interested on predicting and selecting enhanced meal isoflavone and/or oil tocopherol contents.